Effect of Nuclear radiation on polyvinyl chloride - Hussain, Hussain Ali (University of Thi-Qar Journal of Science, 2013)
Charge particle effect have been work out on Polyvinyl chloride ( PVC ) and Nitrate cellulose (CN-85) , this effect have been find out and compared together ( PVC and CN-85 ) , by using optical density technique , this work for this polyvinyl chloride , have been done for the first time .Polyvinyl chloride used in this work, shows more response and more linearity than CN-85, in respond to alpha particle in dose range between 6 mGy to 19 mGy.